KEBIJAKAN TARIF DAN INSENTIF PAJAK PENGHASILAN PADA SEKTOR UMKM BERDASARKAN ASAS EFISIENSI BERKEADILAN DALAM PENANAMAN MODAL (Studi Kasus: UMKMdi Kabupaten Bantul Tahun 2010-2011) - , Mawar Muria Rini; , Adrianto Dwi Nugroho, S.H., Adv LLM. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Micro, Small, Medium Enterprises (MSME) is business group that most found in Bantul. Every year amount of MSME in Bantul increases. Policy on income tax tariff and incentive for MSME in Bantul is expected to be able to push fair, conducive, and competitive business climate. This reseach is according to fair efficiency principle in capital investment, ecspecially for MSME development, then those principal is used by income tax tariff and incentive for tax payer policy for MSME in Bantul. This research indicated that there is different income tax tariff and incentive for tax payer. In MSME group, tariff is differentiated based on personal tax payer and domestic institutional taxpayer and difference in application of tax incentive that only charged to MSME having domestic institutional taxpayer. However, the matter is not barrier for MSME taxpayer to pay income tax. Compliance level of taxpayer to pay income tax in Bantul is high. It indicated that people trust in government in managing the tax that eventually the taxpayer can enjoy it. Government is considered efficient in state revenue through tax, so create conducive and competitive business climate in society, particularly MSME.